SAT-191 Distribution of Annexin A1 (ANXA1) in the Anterior Pituitary Tissue and the Effect on LH Secretion - Fungbun, Numfa (J Endocr Soc, 2019)
We previously showed the stimulatory effect of GnRH on annexin A5 (ANXA5) mRNA expression in the pituitary gonadotropes and the stimulating effect of ANXA5 on gonadotropin secretion (1). Annexin is a family of structurally related 12 proteins in mammals. Although molecular characteristics of annexins, for example calcium dependent phospholipid binding, are shown, their physiological role is still obscure. Among twelve annexins, we have recently reported that the expression of annexin A1 (ANXA1) is also augmented by GnRH in LβT2 gonadotrope cells like as ANXA5 (2). The extent of ANXA1 increase by GnRH, however, was much higher than that of ANXA5. Pituitary ANXA1 was already shown to be involved in cortisol inhibition of ACTH secretion and the expression in the folliculo-stellate cell was demonstrated. In the present study, we examined the distribution of ANXA1 in the pituitary tissues and the effect of ovariectomy. Further, the effect of ANXA1 on LH release in LβT2 gonadotrope was examined. ANXA1 was shown to distribute to majority of anterior pituitary cells and the intensity was highest in folliculo-stellate cell like irregular shaped cells of adult female Wistar Imamichi rats. Pituitary tissues were subjected to immunohistochemistry for ANXA1 after ovariectomy. Large round cells, activated gonadotropes, were appeared two week after the ovariectomy and ANXA1 was distributed to around these cells and folliculo-stellate cell like cells. Nuclear ANXA1 was also prominent. The administration of recombinant human ANXA1 to LβT2 gonadotrope cells increased LH release during 24 h incubation. These results indicate ANXA1 involvement in the regulation of gonadotropin secretion. Although it is not clear why only ANXA1 and A5 out of 12 members are affected by GnRH, these two annexins would be closely related in the gonadotrope. 1) Kawaminami M, Etoh S, Miyaoka H, Sakai M, Nishida M, Kurusu S, Hashimoto I., Annexin 5 messenger ribonucleic acid expression in pituitary gonadotropes is induced by gonadotropin-releasing hormone (GnRH) and modulates GnRH stimulation of gonadotropin release. Neuroendocrinology. 2002 Jan;75(1):2-11. 2) Fungbun N, Tungmahasuk D, Terashima R, Kurusu S, Kawaminami M. Annexin A1 is a novel target gene of gonadotropin-releasing hormone in LβT2 gonadotrope cells. J Vet Med Sci. 2018 Jan 27;80(1):116-124.